PENGARUH INTERAKSI PERLAKUAN Rhizobium DAN PEMUPUKAN NITROGEN TERHADAP INDEKS PANEN TERHADAP TIGA VARIETAS KEDELAI - Makruf Wicaksono; Fitra Syawal Harahap (Jurnal Tanah dan Sumberdaya Lahan, 2020)
The use of nitrogen chemical fertilizers tends to be high in soils with low nitrogen; this can affect the balance of the global N cycle. One alternative to minimize the above problem is to optimize the utilization of biological nitrogen fixation. The purpose of this study was to determine the effect of increased nitrogen uptake of yields and some soybean varieties. The study was conducted using a split plot design that consisted of three factors where the first factor was Rhizobium (R) inoculation, the second factor was soybean (V) variety, and the third factor was N (N) fertilizer. Results of this study showed that the N fertilization treatment gave a significant response while Rhizobium (R) treatment and variety (V) did not provide a significant response to the harvest index parameters. The interaction of varieties and N fertilization (VxN) gave a significant response while the interaction of Rhizobium and varieties (RxV), Rhizobium and N (RxN), Rhizobium fertilization, varieties and N (RxVxN) fertilization did not provide a significant response to the harvest index. The highest Index was Wilis variety that was harvested without N (V3N0) fertilization but was not significantly different from V3N1, V3N2 and V3N3. The production of soybean seeds had not been able to increase ESN because the plant dry weight and N uptake were not comparable.Â Â Â